Perceptions and experiences of users with chronic kidney disease in a hemodialysis service (Research, Society and Development, 2023)
Objective: to know the perception and experience of users with chronic renal failure (CRF) in a Hemodialysis service. Method: qualitative descriptive and exploratory study, carried out in a hemodialysis service in the interior of the state of São Paulo; with CRF patients being treated in this field of study. Data collection was carried out through the application of a questionnaire containing questions about the sociodemographic profile, about their perception and experience in the studied service. Bardin's Content Analysis was used. Results: 22 patients participated, with a mean age of 58 years (SD=14.18), male 17 (77.2%), complete high school 12 (54.5%) and without employment activity 20 (90.9%). Regarding the perception of the diagnosis of CRF, they revealed feelings of fear, uncertainty, lack of knowledge and concern. As for the experience with the disease and hemodialysis treatment, they pointed out difficulties with regard to nutrition, commuting to the unit, session time, making and puncture of the fistula. They showed good rapport, bond, partnership and coexistence with the professionals of this unit and pointed out aspects of improvement in work processes, comfort, food offered and in the human resources framework. Conclusion: the perception and experience of patients with CRF in this hemodialysis unit showed the difficulties in coping with the disease and the strengthening resulting from professional and patient relationships, making the treatment promising, effective and with quality.